Revitalizing self-help spirit in the communities: Are there roles for adult educators to play?. Issue 3 (27th May 2022) - Biney, Isaac Kofi
ABSTRACT: Self-help spirit which culminates into selfless services, voluntarism, and free labor by people in communities appears to be waning in Ghana. This free labor services provided by community members require revitalization. Adult educators have roles to play in revitalizing self-help spirit to build resilient communities., Questions to be addressed are: What is self-help in community development? Who are adult educators and what roles they play in reviving self-help spirit in the communities? This theoretical approach to literature review paper used a library research and adapted a critical literature review approach. It reviewed 30 out of the 60 documents on self-help, adult educators, and community development. It was observed that self-help, a strategy to improve communities, makes people learn. Through continuous learning and training, people adapt to changes and address problems in their communities. Adult educators are to build inclusiveness, networks, attitudinal change, partnership and mobilization of self-help groups to restore vitality and make communities more vibrant and sustainable.